Conservative therapy for acromioclavicular joint dislocation - Rockwood III: a cohort analysis - Kovařík, J; Krtička, M; Ira, D; Dráč, P; Benešová, K; Korpa, P (Rozhledy v chirurgii, 2024)
INTRODUCTION: Acromioclavicular joint dislocation (AC) - Rockwood III (RIII) is a controversial topic with a wide range of therapeutic approaches. Operative therapy offers dozens of stabilization methods, which only confirms the absence of a "gold standard". The currently available literature tends to favor conservative therapy, involving several consecutive phases of physiotherapeutic care after the pain has subsided. The aim is to gradually improve the mobility of the shoulder and subsequently strengthen and stabilize the entire shoulder girdle. METHODS: A study was conducted between 01/2014 and 12/2017 in patients with Rockwood III type AC joint injury. Each patient was educated in detail about the surgical and conservative treatment options and expected outcomes. Patients who opted for conservative therapy were invited to evaluate the results of the therapy at a minimum of one year after the injury. Each patient was clinically examined. Coracoclavicular (CC) distances were measured, and the presence of arthrosis and calcifications was assessed on follow-up comparison scans of both shoulders. The Constant Score (CS) and the American Shoulder and Elbow Surgeons (ASES) score were evaluated in the patients. The results were statistically processed and compared to each other and/or to the healthy shoulder. RESULTS: A total of 37 patients were evaluated with a mean CS of 96.1 and a mean ASES score of 92.02. Lateral clavicle instability was found in 64% of the patients (n=24). The mean difference of the CC interval versus the healthy side was 8.6 mm. There was no statistically significant difference between the CS of the injured and healthy shoulder. No statistically significant association was found between CS and lateral clavicle prominence, AC joint stability, and workload, or between return to work and workload. CONCLUSION: Conservative therapy of AC joint dislocation - type RIII provides good functional outcomes.
Keywords: akromioklavikulární kloub; Cohort Studies; Rockwood III; dislokace kloubu; Middle Aged; mužské pohlaví; Adult; Joint Dislocations; kohortové studie; acromioclavicular dislocation; ženské pohlaví; Humans; konzervativní terapie; Acromioclavicular Joint; Physiotherapy; lidé středního věku; rehabilitation; dospělí; Female; Conservative Treatment; conservative therapy; lidé; Male